DNA methylation and SNP in IFITM3 are correlated with hand, foot and mouth disease caused by enterovirus 71. (April 2021) - Li, Mei; Li, Ya-Ping; Deng, Hui-Ling; Wang, Mu-Qi; Chen, Yuan; Zhang, Yu-Feng; Wang, Jun; Dang, Shuang-Suo
Highlights: Hand, foot and mouth disease induced by enterovirus 71 (EV71-HFMD) can lead to high morbidity and mortality. Interferon-induced transmembrane protein 3 (IFITM3) is an antiviral protein. Its overexpression can suppress the infection efficiency of many viruses. IFITM3 single-nucleotide polymorphism (SNP) genotype, promoter methylation and mRNA expression of peripheral blood mononuclear cells were correlated with the progression of EV71 infection, especially in patients with severe EV71-HFMD. IFITM3 methylation status and SNP genotype may help clinicians to choose the correct treatment strategy for patients with EV71-HFMD. Abstract: Objectives: To explore the mechanisms of interferon-induced transmembrane protein 3 (IFITM3) in response to enterovirus-71-associated hand, foot and mouth disease (EV71-HFMD), in terms of DNA methylation, single-nucleotide polymorphism (SNP) genotype and gene expression. Methods: In total, 120 patients with EV71-HFMD (60 with mild EV71-HFMD and 60 with severe EV71-HFMD) and 60 healthy controls were enrolled in this study. SNP genotype, IFITM3 promoter methylation and mRNA expression of peripheral blood mononuclear cells were examined using the improved multi-temperature ligase detection reaction, quantitative reverse transcriptase polymerase chain reaction and MiSeq, respectively. Results: The distribution of methylation in patients with EV71-HFMD was significantly lower compared with healthy controls, and the severe EV71-HFMD group showed the lowest frequency of IFITM3 promoter methylation. The average level of IFITM3 promoter CpG methylation was negatively correlated with IFITM3 mRNA expression, and hypermethylation of several specific CpG units contributed to IFITM3 downregulation. IFITM3 expression and promoter methylation correlated with EV71 infection progression, especially in the severe EV71-HFMD group. Compared with mild cases, genotype GG and the G allele of rs12252 were over-represented in patients with severe EV71-HFMD. Conclusions: IFITM3 methylation status and SNP genotyping may help clinicians to choose the correct treatment strategy for patients with EV71-HFMD.